PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) (Studi kasus pada Bank Umum Swasta Nasional Devisa Go Public di Bursa Efek Indonesia Periode 2009-2010) - Latifah, Nurul Maulidya; Rodhiyah, Rodhiyah; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2012)
Bank as a company have their health assessed to determine the condition of the bank. Least healthy financial performance of banks can be seen through the performance of the bank's profitability. The ratio is important for bank profitability is return on assets (ROA). Data from the period 2009-2010 the average ROA bank has shown a good value with a standard sound bank is above 1.5%. However, the ROA between the bank and the private limited company visible difference, namely the value of the bank's ROA persero higher than private banks. ROA is the high and low values ​​are caused by several factors such as differences in the ratio of the associated CAR, NPL, and the LDR. The purpose of this study to analyze the effect of Capital Adequacy Ratio (CAR), non-performing loans (NPL), and the Loan to Deposit Ratio (LDR) to the Return On Asset (ROA) of the National Private Banks Foreign exchange go public in Indonesia Stock Exchange in the period research from 2009 to 2010. The analytical method used is a simple regression test to test partially the significance test using t test and regression test to simultaneously test for the significance test using the F test, which previously made ​​the assumption of classical test analysis techniques first. Object of this study is a national private commercial bank foreign exchange 2009-2010. Number of samples used were 24 banks in the sample. With certain criteria that companies belonging to banking in commercial banks to go public and has published its financial statements in the year 2009-2010. Results and discussion indicate that the NPL variables significantly influence the ROA, while the CAR and the LDR variable is not significant to the ROA. While based on the results of simultaneous hypothesis tests (F test) showed that the CAR, NPL, and the LDR has a significant effect on ROA with a significance level of 0.000. Adjusted R2 values ​​obtained in the regression model of 0.835. This suggests that the major influence of the independent variable is CAR, NPL, and the LDR of the dependent variable (ROA) of 83.5% while the remaining 16.5% influenced by other factors. In addition the value of R2 is the R2 value of 0.835 indicates if it is getting closer to a variable - the independent variable (CAR, NPL, and LDR) the stronger influence in explaining the dependent variable (ROA). Overall conclusions of the independent variables studied, the ratio of the greatest influence on the dependent variable is the ratio of NPLs at 82.6% and showed a significant effect of t -14.597 0.000 with significance. It means that the greater the ratio of Non Performing Loan (NPL) cause Return On Asset (ROA) is getting smaller at a bank. Proposed research should better supervise banking companies and credit funds in order to monitor the use of non-performing loans ratio remained at a healthy category so as to avoid the problem of bad loans.